Philippines : 2009 Article IV Consultation-Staff Report, Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Philippines. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This 2009 Article IV Consultation highlights that following the adverse impact from the global economic and financial crisis, there are signs of a nascent recovery of the Philippine economy. Growth is expected at 3/4 percent in 2009 and to recover to about 3u percent in 2010. The recovery will likely be led by private consumption as confidence strengthens and remittances pick up further. Investments and exports are also expected to benefit from the global recovery. Risks to the near-term outlook are broadly balanced and sensitive to the global growth outturn.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet